A method for stabilizing steel slag and application thereof

CN122958078APending Publication Date: 2026-10-23WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098393.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]目前,改善钢渣安定性的主流技术均存在明显局限:物理陈化周期漫长(数月以上),效率低下;化学改性可能引入污染且成本较高;碳化处理虽效果较好,但通常需在高压、加热条件下进行,设备要求高、能耗大且处理时间仍长达24小时以上

Benefits of technology

(1)本发明利用电场主动驱动钢渣中有害离子(Ca2+)的定向迁移与转化,突破了传统方法依赖自然扩散或外部压力渗透的速率瓶颈。如实施例1所示,在常温常压下,仅需10分钟处理即可使钢渣的游离氧化钙含量平均降低80%以上,其中钢渣粉的f-CaO降解率可超过97%。其处理效率较长达数月至数年的自然陈化法提升数个数量级,也远优于处理周期通常在24小时以上的传统碳化工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958078A_ABST
    Figure CN122958078A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of steel slag's stabilization treatment method and application, belong to building material and solid waste resource technology field.The core step includes: preparation includes specific conductive metal salt and sodium bicarbonate electrolyte solution;With free calcium oxide containing steel slag is placed in the anode region of electrolytic device, electrolysis is carried out under normal temperature and pressure by applying direct current voltage, while the CO2 containing industrial waste gas is introduced into anode region;After electrolysis, steel slag is post-treated, and the stabilized product is obtained.The present application utilizes the principle of electrochemical migration and conversion, drives the free calcium oxide inside steel slag to quickly ionize, directional migration and combine with carbonate, forms stable calcium carbonate coating on the surface of steel slag, so as to realize efficient stabilization in very short time.The method has the advantages of fast processing speed, mild conditions, low energy consumption, can realize "waste treatment with waste" and the like, and the treated steel slag product has excellent stability, which can be directly used to prepare asphalt concrete, cement stabilized base and other building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials and solid waste resource utilization technology, and in particular to a method for stabilizing steel slag and its application. Background Technology

[0002] With increasingly stringent global environmental policies and continuous infrastructure construction, the contradiction between the limited mining of natural sand and gravel aggregates and the large-scale stockpiling of industrial solid waste steel slag is becoming increasingly prominent. Utilizing steel slag as a building aggregate is an ideal way to simultaneously address resource shortages and environmental pressures. Research shows that steel slag possesses excellent physical and mechanical properties, making it a potentially high-quality substitute for natural aggregates in asphalt and cement concrete.

[0003] However, the abundant free calcium oxide in steel slag severely restricts its engineering applications. f-CaO undergoes a hydration reaction upon contact with water, producing calcium hydroxide accompanied by significant volume expansion, leading to cracking and damage in concrete structures using it as aggregate—in other words, poor volume stability. This fundamental material defect is a technical bottleneck that must be overcome for the large-scale, high-value-added resource utilization of steel slag.

[0004] Currently, mainstream technologies for improving the stability of steel slag all have significant limitations: physical aging has a long cycle (several months or more) and low efficiency; chemical modification may introduce pollution and is costly; while carbonization treatment is effective, it usually requires high pressure and heating conditions, demanding sophisticated equipment, consuming large amounts of energy, and still taking more than 24 hours. Therefore, there is an urgent industrial need to develop a new technology that can achieve ultra-rapid stabilization of steel slag under mild conditions of ambient temperature and pressure. Summary of the Invention

[0005] In view of this, the present invention proposes a stabilization treatment method that can quickly and efficiently eliminate the hazards of free calcium oxide in steel slag under normal temperature and pressure conditions, and realize the direct application of the treated steel slag in high-grade road engineering and building materials.

[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a method for stabilizing steel slag, comprising the following steps: S1. Dissolve the conductive metal salt and bicarbonate compound in water to form an electrolyte solution; S2. Place the steel slag raw material containing free calcium oxide in the anode area of ​​the electrolysis device, and insert the anode and cathode into the electrolyte solution obtained in step S1; apply DC voltage for electrolysis, and at the same time introduce industrial waste gas containing CO2 into the anode area; S3. After electrolysis, the steel slag and electrolyte solution are separated. The steel slag is then dried, magnetically separated, and sieved to obtain a stabilized steel slag product.

[0007] Based on the above technical solutions, the preferred method of this invention utilizes the strongly acidic local environment generated in the anode region during electrolysis to rapidly ionize free calcium oxide within the steel slag into calcium ions. Under the influence of a DC electric field, these calcium ions migrate directionally towards the cathode region. Simultaneously, the introduced CO2 forms bicarbonate / carbonate ions in the electrolyte, which combine with the migrating calcium ions to generate stable calcium carbonate. This calcium carbonate can deposit on the surface and pores of the steel slag particles, forming a dense coating layer. This process achieves both "electrochemically driven migration" and "in-situ stabilization" of harmful components within the steel slag, thereby solving the problem of volume expansion in a very short time.

[0008] More preferably, in step S1, the conductive metal salt is selected from at least one of sodium chloride, sodium sulfate, and calcium chloride; the bicarbonate compound includes sodium bicarbonate.

[0009] More preferably, the total mass concentration of the conductive metal salt in the electrolyte solution is 2%-15%; and the mass concentration of the bicarbonate compound in the electrolyte solution is 2%-10%. All concentrations are percentages of the solute mass relative to the total mass of the electrolyte solution.

[0010] More preferably, the resistivity of the electrolyte solution is ≥5kΩ.

[0011] More preferably, in step S2, the DC voltage ranges from 10V to 110V. Voltage is a key parameter driving the electrochemical migration reaction. When the voltage is too low, the electric field strength is insufficient, resulting in a weak driving force for ion migration in the solution, hindering the ionization of f-CaO and Ca... 2+ The migration rate is slow, and the stabilization effect is not significant. Excessive voltage causes violent electrolysis of water, increases side reactions, surges energy consumption, and poses operational safety hazards.

[0012] More preferably, in step S2, the volume concentration of CO2 in the CO2-containing industrial waste gas is ≥20%. Introducing CO2 not only provides the necessary reactants for the conversion of f-CaO to calcium carbonate, which is a core step in achieving ultra-fast stabilization of steel slag, but also utilizes the steel slag itself as a carbon fixation medium, achieving the fixation of CO2 in the industrial waste gas, thus providing environmental benefits.

[0013] More preferably, the CO2-containing industrial waste gas is introduced for 1-20 minutes.

[0014] More preferably, the particle size range of the steel slag raw material is 0.075mm-32mm; wherein the free calcium oxide content of the steel slag raw material is 4%-8%.

[0015] Secondly, the present invention also provides a steel slag product prepared by the above method, wherein the free calcium oxide content is stably below 1.5%, which meets the stability requirements for engineering applications.

[0016] Thirdly, the present invention further provides the application of the stabilized steel slag product in building materials, specifically it can be used to prepare various types of asphalt concrete (such as SMA-13, AC-20, AC-25), cement-stabilized crushed stone base course and steel slag-based cementitious materials.

[0017] The present invention has the following advantages over the prior art: (1) This invention utilizes an electric field to actively drive harmful ions (Ca) in steel slag. 2+ The targeted migration and transformation of calcium oxide in steel slag breaks through the rate bottleneck of traditional methods that rely on natural diffusion or external pressure infiltration. As shown in Example 1, under normal temperature and pressure, only 10 minutes of treatment is needed to reduce the free calcium oxide content of steel slag by an average of more than 80%, and the f-CaO degradation rate of steel slag powder can exceed 97%. Its treatment efficiency is several orders of magnitude higher than that of natural aging methods that take months to years, and it is also far superior to traditional carbonization processes that usually have a treatment cycle of more than 24 hours.

[0018] (2) The entire process is carried out at room temperature (20-30℃) and normal pressure, without relying on high-pressure reactors or heating devices, which fundamentally eliminates the risks of large equipment investment, high energy consumption and operational safety associated with high-pressure and high-temperature processes. This method has simple equipment requirements and low operating costs, providing feasibility for large-scale, continuous industrial processing of steel slag.

[0019] (3) This method can directly utilize recovered waste gas rich in CO2 (concentration ≥20%) generated by steel plants or other industrial processes as reaction raw materials. While treating steel slag solid waste, the CO2 in the waste gas is converted into stable calcium carbonate and fixed in the steel slag product, realizing the synergistic resource utilization of "solid waste" and "waste gas", which also has the function of carbon fixation and is in line with the concept of circular economy and green development. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is the gradation curve diagram used in Application Example 1 of the present invention to prepare AC-25 asphalt concrete; Figure 2This is the gradation curve diagram used in Application Example 1 of the present invention to prepare AC-20 asphalt concrete; Figure 3 This is the gradation curve diagram used in Application Example 1 of the present invention to prepare SMA-13 ​​asphalt concrete; Figure 4 This is a gradation curve diagram used in Application Example 1 of the present invention to prepare cement-stabilized crushed stone base course. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] like Figures 1-4 As shown, the upper limit of the AC-25, AC-20, SMA-13, and steel slag cement stabilized base courses prepared in Example 1 of this invention is the maximum value of the mineral aggregate passing rate for each sieve size. If the production mix proportion curve runs above the upper limit of the gradation, it indicates that there is too much fine material and too little coarse material, and the mixture will be too soft and easily deformed; the lower limit is the minimum value of the mineral aggregate passing rate for each sieve size. If the production mix proportion curve runs below the lower limit of the gradation, it indicates that there is too much coarse material and too little fine material, and the mixture will be too hard, easily cracked, and have a high porosity; the production mix proportion gradation curve is the final mineral aggregate gradation curve determined after sampling, screening, and trial mixing adjustments in the hot silo of the mixing plant, and is used to guide on-site construction. This curve falls entirely between the upper and lower limits, indicating that the mineral aggregate gradation of this production mix proportion meets the specifications. Among them, the mix proportion of steel slag cementitious materials (mortar) is shown in Table 1 below.

[0024] Table 1: Mix proportions of steel slag cementitious materials This embodiment uses hot-quenched steel slag provided by a steel plant in Wuhan. The chemical composition of the steel slag is shown in Table 2 below.

[0025] Table 2: Chemical composition of steel slag raw materials in Examples 1-3 and Comparative Examples 4-8 The CaO in the table includes both inactive calcium oxide and active free calcium oxide.

[0026] Example 1: S1. Prepare the electrolyte in a corrosion-resistant container using 1L of distilled water as the solvent. Specifically: Weigh 50g of sodium chloride, 30g of sodium sulfate, 20g of calcium chloride, and 50g of sodium bicarbonate, and stir until completely dissolved to obtain an electrolyte solution with a total volume of approximately 1050g. Its initial pH is 5.3, and its resistivity is greater than 5 kΩ·cm.

[0027] S2. Place 500g of unscreened mixed steel slag with a particle size ranging from 0.075mm to 32mm in the anode zone of the electrolytic cell, and insert the anode and cathode into the electrolyte solution. Electrolysis is performed at 25℃ with a DC voltage of 60V, while simultaneously introducing steel mill recovered waste gas with a CO2 volume concentration of 25% into the anode zone at a constant flow rate. The electrolysis and gas introduction process lasts for 10 minutes.

[0028] S3. After electrolysis, the steel slag is separated from the electrolyte solution. After draining and drying at 105℃ to constant weight, the steel slag is first subjected to magnetic separation to remove metallic iron, and then screened into stabilized products of different particle sizes using a standard vibrating screen, including coarse aggregates of 3-5mm, 5-10mm, 10-15mm, 15-20mm, and 20-32mm, fine aggregates of 0.075-3mm, and steel slag powder smaller than 0.075mm.

[0029] Example 2: S1. Prepare the electrolyte in a corrosion-resistant container using 1L of distilled water as the solvent. Specifically: Weigh 20g of sodium chloride and 20g of sodium bicarbonate, stir until completely dissolved, and obtain the electrolyte solution. Its initial pH is 7.5, and its resistivity is greater than 5 kΩ·cm.

[0030] S2. Place 500g of unscreened mixed steel slag with a particle size range of 0.075mm to 32mm in the anode zone of the electrolytic cell, and insert the anode and cathode into the electrolyte solution. Electrolyze under a DC voltage of 10V at 20℃, while simultaneously introducing steel mill recovered waste gas with a CO2 volume concentration of 20% into the anode zone at a constant flow rate. The electrolysis and gas introduction process lasts for 5 minutes.

[0031] S3. Post-processing operations are the same as in Example 1.

[0032] Example 3: S1. Prepare the electrolyte in a corrosion-resistant container using 1L of distilled water as the solvent. Specifically: Weigh 100g of sodium chloride, 30g of sodium sulfate, 20g of calcium chloride, and 100g of sodium bicarbonate, and stir until completely dissolved to obtain the electrolyte solution. Its initial pH is 8.1, and its resistivity is greater than 5 kΩ·cm.

[0033] S2. Place 500g of unscreened mixed steel slag with a particle size ranging from 0.075mm to 32mm in the anode zone of the electrolytic cell, and insert the anode and cathode into the electrolyte solution. Electrolysis is performed at 30℃ with a DC voltage of 110V, while simultaneously introducing steel mill recovered waste gas with a CO2 volume concentration of 25% into the anode zone at a constant flow rate. The electrolysis and gas introduction process lasts for 10 minutes.

[0034] S3. Post-processing operations are the same as in Example 1.

[0035] Comparative Example 4: The difference between this comparative example and Example 1 is that the steel slag raw material was treated using the industry-standard natural aging method. Other steps, such as the source of raw materials and testing methods, are the same as in Example 1 and will not be repeated here.

[0036] Specific procedures: Take steel slag raw materials from the same batch and particle size range as in Example 1, and store them naturally in an open-air environment for a 6-month aging process. This method utilizes the moisture and carbon dioxide in the environment to slowly dissolve the free calcium oxide in the steel slag, which is a traditional physical stabilization method in the industry.

[0037] Comparative Example 5: The difference between this comparative example and Example 1 is that the steel slag raw material was treated using the traditional carbonization stabilization technology, while the remaining steps were the same as in Example 1.

[0038] Specific operation: Using molten steel slag as raw material, industrial waste gas containing CO and CO2 is introduced during the hot slag cooling process to carry out primary carbonization; then steel slag smaller than 10mm is screened and the same waste gas is introduced under pressure to carry out secondary carbonization, and finally the product is obtained by magnetic separation.

[0039] Comparative Example 6: The difference from Example 1 is that 1L of distilled water was used as the solvent, and 10g of sodium chloride and 10g of sodium bicarbonate were weighed and dissolved by stirring. In the resulting solution, the mass concentration of sodium chloride was approximately 1.0%, and the mass concentration of sodium bicarbonate was approximately 1.0%. The remaining steps were the same as in Example 1.

[0040] Comparative Example 7: The difference from Example 1 is that 150g of sodium chloride, 30g of sodium sulfate, 20g of calcium chloride, and 120g of sodium bicarbonate were weighed and dissolved by stirring in 1L of distilled water as solvent. In the resulting solution, the mass concentration of sodium chloride was approximately 20.0%, and the mass concentration of sodium bicarbonate was approximately 12.0%. The remaining steps were the same as in Example 1.

[0041] Comparative Example 8: The difference from Example 1 is that CO2 is not introduced in step S2, while the other steps are the same as in Example 1.

[0042] Table 3: f-CaO content of Examples 1-3, Comparative Examples 4-8 and untreated steel slag raw materials Table 3 shows that the f-CaO content of steel slag aggregate underwent drastic changes during electrolysis. The degradation rate of f-CaO content in steel slag aggregate showed a negative correlation with particle size. This is because steel slag powder has the largest specific surface area, which allows it to accept more charge and CaO. 2+ The precipitation rate was higher, thus achieving complete degradation of f-CaO content within 10 minutes. Meanwhile, the inventors discovered that the degradation of f-CaO content in steel slag coarse aggregate is limited due to factors such as specific surface area. Therefore, the electrolysis time for steel slag coarse aggregate larger than 5mm was extended to achieve a superior carbonization effect.

[0043] Comparing Comparative Examples 6-7 with Example 1, it is evident that when the mass concentration of the solute in the electrolyte solution is too low (e.g., the concentrations of sodium chloride and sodium bicarbonate in Comparative Example 6 are both approximately 1.0%) or too high (e.g., sodium chloride approximately 20.0% and sodium bicarbonate approximately 12.0% in Comparative Example 7), the system's ability to guarantee comprehensive carbonization of steel slag is limited. According to the test results in Table 2, under the specific electrolyte ratio set in Example 1, the f-CaO content of fine aggregates smaller than 3 mm and steel slag powder achieved extremely deep degradation (as low as 0.1%~0.7%); while the f-CaO content in Comparative Examples 6 and 7, within the same particle size range, remained at 1.0%~1.2% and 0.8%~1.0%, respectively, with degradation effects inferior to Example 1. This indicates that a specific electrolyte concentration ratio is a crucial process parameter for enhancing the deep carbonization effect of fine-particle steel slag.

[0044] A comparison of Comparative Example 8 and Example 1 shows that simple electrolytic treatment cannot effectively eliminate f-CaO, and simple CO2 carbonization cannot complete the reaction in such a short time under normal temperature and pressure. Under pure electrolytic conditions where only DC voltage is applied but no CO2 gas is introduced (Comparative Example 8), the f-CaO content of steel slag of various particle sizes after treatment is still at a relatively high level of 1.3%~2.7%. In contrast, under the same electric field conditions with simultaneous introduction of CO2 gas (Example 1), the f-CaO content of steel slag of various particle sizes is significantly reduced to 0.1%~1.8%. This significant difference directly confirms that the removal capacity of single electrolytic treatment for f-CaO is limited. Only when the electrochemical environment and CO2 gas work together can efficient and thorough carbonization of mixed steel slag of multiple particle sizes be activated and achieved.

[0045] Application Example 1: The steel slag prepared in Example 1 and Comparative Examples 4-5 were used to prepare SMA-13 ​​steel slag asphalt concrete, AC-20 steel slag asphalt concrete, AC-25 steel slag asphalt concrete, steel slag water-stabilized base course and steel slag cementitious material, respectively, in accordance with the Technical Specifications for Construction of Highway Asphalt Pavement (JTG / TF40-2004) and the Technical Details for Construction of Highway Pavement Base Course (JTG / TF20-2015).

[0046] (1) Preparation of SMA-13 ​​steel slag asphalt concrete: According to the "Technical Specification for Construction of Highway Asphalt Pavement" (JTG F40-2004), the prepared steel slag product was screened and batched according to the SMA-13 ​​standard gradation requirements (mainly using 5~15mm steel slag as coarse aggregate, with an appropriate amount of fine aggregate). The batched steel slag aggregate was placed in an oven and heated to 175℃~185℃ for later use. In a constant temperature mixing pot, the hot aggregate and lignin fiber (0.3% of the total mass of the aggregate) were first added and dry-mixed for 90 seconds; then SBS modified asphalt preheated to 165℃~175℃ was added and mixed for another 90 seconds; finally, preheated mineral powder was added and mixed for 90 seconds until the mixture was uniform and free of white spots, thus obtaining the SMA-13 ​​mixture.

[0047] (2) Preparation of AC-20 and AC-25 steel slag asphalt concrete: According to the target mix proportions of AC-20 and AC-25, weigh the corresponding coarse and fine aggregates of steel slag and combine them for gradation (the maximum nominal particle size of AC-20 is 19 mm, and the maximum nominal particle size of AC-25 is 26.5 mm). Heat the mixed aggregates to 160℃~170℃. Add the hot aggregates to the mixing pot and dry mix for 60 seconds, then add asphalt (70# heavy traffic road petroleum asphalt or SBS modified asphalt) preheated to 150℃~160℃ and wet mix for 90 seconds; finally, add mineral powder and continue mixing for 90 seconds, and the AC-20 and AC-25 steel slag asphalt concretes are obtained by discharge.

[0048] (3) Preparation of steel slag water-stabilized base course mixture: According to the "Technical Specifications for Construction of Highway Pavement Base Course" (JTG / T F20-2015), the coarse and fine aggregates of various particle sizes of the prepared steel slag are mixed according to the base course gradation requirements. Ordinary Portland cement is added according to a specific proportion of the dry weight of the mixture (e.g., 4%~6%), and dry mixing is carried out at room temperature to make the cement and steel slag evenly mixed. Subsequently, according to the optimum moisture content of the gradation determined in advance by heavy compaction test, an appropriate amount of water is added to the mixture, and a forced mixer is used to mix it thoroughly for 3~5 minutes until the moisture is evenly distributed and there are no dry material lumps, thus obtaining the steel slag cement stabilized base course mixture.

[0049] (4) Preparation of steel slag cementitious material: Take the treated steel slag powder smaller than 0.075 mm as the core active material, mix it with silicate cement (or slag powder, fly ash and other auxiliary materials) at the set mass ratio; after thorough mixing, add mixing water according to the standard consistency water volume or the set water-cement ratio, and use a standard cement paste mixer to slowly stir for 2 minutes, stop stirring for 15 seconds, and then stir quickly for 2 minutes to obtain a uniform steel slag cementitious material slurry. The slurry can be injected into a standard mold and molded and tested under standard curing conditions.

[0050] The stability and mechanical properties of steel slag asphalt concrete, steel slag water-stabilized base course, and steel slag cementitious materials were tested in accordance with the "Specifications for Testing Aggregates in Highway Engineering" JTG 3432-2024, "Stability Test Methods for Steel Slag" GB / T24175-2009, and "Specifications for Testing Asphalt and Asphalt Mixtures in Highway Engineering" JTG E20-2011.

[0051] Table 4 shows the expansion rate test data for SMA-13, AC-20, and AC-25 steel slag asphalt concrete. The results of the water immersion expansion test indicate that the expansion rate of all steel slag asphalt concretes was significantly increased after electrolytic treatment. Among them, SMA-13, as the surface layer of asphalt pavement, has the highest probability of contact with water and poses the greatest safety risk. After electrolysis, the expansion rate of SMA-13 ​​steel slag asphalt concrete decreased from 4.1% to 1.1%, the expansion rate of AC-20 steel slag asphalt concrete decreased from 5.2% to 1.0%, and the expansion rate of AC-25 steel slag asphalt concrete decreased from 3.2% to 0.5%.

[0052] Table 4: Expansion Test of Steel Slag Asphalt Concrete The experimental results comprehensively demonstrate that reducing the free calcium oxide (f-CaO) content in steel slag plays a crucial role in improving the long-term stability of composite materials in different systems. Firstly, in asphalt concrete systems, the reduction in f-CaO content directly enhances the stability of the aggregate skeleton, as evidenced by the fact that SMA-13 ​​mixture maintains a high residual stability of 93.1% after a high-temperature water bath. Simultaneously, in cement-based materials, the data in Table 5 show that reducing the f-CaO content (especially controlling it below 0.5%) significantly inhibits hydration expansion, fundamentally improving the volume stability of cement-stabilized base courses and steel slag cementitious materials, almost completely avoiding damage caused by expansion.

[0053] Table 5: High-Temperature Residual Stability of Steel Slag Asphalt Concrete Table 6: Expansion Test of Steel Slag Water-Stabilized Layer and Steel Slag Cementitious Material In summary, the comparison of multi-system test data shows that the process of this invention, through the complete degradation of f-CaO, achieves a qualitative leap in core technical indicators such as anti-expansion performance and residual stability of the prepared SMA-13, AC-20, and AC-25 steel slag asphalt concrete, steel slag water-stabilized base course, and steel slag cementitious materials. This process overcomes the stability problem of steel slag utilization in building materials and has excellent engineering application and promotion value.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for stabilizing steel slag, characterized in that, Includes the following steps: S1. Dissolve the conductive metal salt and bicarbonate compound in water to form an electrolyte solution; S2. Place the steel slag raw material containing free calcium oxide in the anode area of ​​the electrolysis device, and insert the anode and cathode into the electrolyte solution obtained in step S1; apply DC voltage for electrolysis, and at the same time introduce industrial waste gas containing CO2 into the anode area; S3. After electrolysis, the steel slag and electrolyte solution are separated. The steel slag is then dried, magnetically separated, and sieved to obtain a stabilized steel slag product.

2. The processing method as described in claim 1, characterized in that, In step S1, the conductive metal salt is selected from at least one of sodium chloride, sodium sulfate, and calcium chloride; the bicarbonate compound includes sodium bicarbonate.

3. The processing method as described in claim 2, characterized in that, The total mass concentration of the conductive metal salt in the electrolyte solution is 2%-15%; the mass concentration of the bicarbonate compound in the electrolyte solution is 2%-10%.

4. The processing method as described in claim 1, characterized in that, In step S2, the electrolysis is carried out at a temperature of 20℃-30℃.

5. The processing method as described in claim 1, characterized in that, In step S2, the range of the DC voltage is 10V-110V.

6. The processing method as described in claim 1, characterized in that, In step S2, the volume concentration of CO2 in the CO2-containing industrial waste gas is ≥20%.

7. The processing method as described in claim 6, characterized in that, The CO2-containing industrial waste gas is introduced for 5-10 minutes.

8. The processing method as described in claim 1, characterized in that, The particle size range of the steel slag raw material is 0.075mm-32mm; the free calcium oxide content is 4%-8%.

9. A steel slag product, characterized in that, The steel slag product is prepared by the processing method according to any one of claims 1-8.

10. The application of the steel slag product as described in claim 9 in building materials.